2010
DOI: 10.1016/j.fertnstert.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin E–binding protein afamin is altered significantly in the peritoneal fluid of women with endometriosis

Abstract: The objective of this case-control study of 242 reproductive-age women was to determine the concentration of afamin in the serum and peritoneal fluid of women with and without endometriosis and to test afamin as a diagnostic marker of endometriosis. Afamin levels were altered significantly in the peritoneal fluid of women with endometriosis compared with disease-free controls, correlated with vitamin E levels, and are consistent with increased oxidative stress in the peritoneal cavity of women with endometrios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…These results were later validated in an independent larger study of patients with ovarian cancer [17] and, very recently, extended by showing significant associations between afamin plasma concentrations and clinical outcomes (response to therapy and survival rates) [24]. In contrast, afamin concentrations were not found to be decreased in benign gynecological conditions including endometriosis [17,25].…”
Section: Clinical Applications Of Afamin Measurementmentioning
confidence: 80%
“…These results were later validated in an independent larger study of patients with ovarian cancer [17] and, very recently, extended by showing significant associations between afamin plasma concentrations and clinical outcomes (response to therapy and survival rates) [24]. In contrast, afamin concentrations were not found to be decreased in benign gynecological conditions including endometriosis [17,25].…”
Section: Clinical Applications Of Afamin Measurementmentioning
confidence: 80%
“…Completely opposite results were presented by Jackson et al [13]. Observations of PF vitamin E concentration are also inconsistent [14,15,16]. Szczepańska et al [9] demonstrated lower total antioxidant status in PF of infertile women with endometriosis.…”
Section: Introductionmentioning
confidence: 93%
“…Afamin was therefore suggested as playing a role in female fertility [92] , and indeed it has been shown to bind vitamin E and to increase in maternal serum during pregnancy [92] . Yet the precise role of afamin in pregnancy or for infertility is still not known [95] . On the one hand, afamin increases during pregnancy and decreases after childbirth to baseline levels, but on the other hand, a pilot study of Hubalek et al [92] showed that women suffering from pregnancy complications had significantly higher median afamin concentrations than women with uncomplicated pregnancy.…”
Section: Afaminmentioning
confidence: 99%